2020
DOI: 10.1177/8755293019878187
|View full text |Cite
|
Sign up to set email alerts
|

A domestic earthquake impact alert protocol based on the combined USGS PAGER and FEMA Hazus loss estimation systems

Abstract: The United States Geological Survey’s Prompt Assessment of Global Earthquakes for Response (PAGER) alert system provides rapid (10–20 min) but general loss estimates of ranges of fatalities and economic impact for significant global earthquakes. FEMA’s Hazus software, in contrast, provides time-consuming (2–5 h) but more detailed loss information quantified in terms of structural, social, and economic consequences estimated at a much higher spatial resolution for large domestic earthquakes. We developed a rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Several studies have worked on validating and comparing losses from Hazus to real events (Kircher et al, 2006; National Institute of Building Sciences (NIBS), 2001; Remo and Pinter, 2012; Wald et al, 2020). The NIBS (2001) study examined only earthquakes in California and found that using site-specific soil types and actual building inventories could improve loss estimates by 10%–30% and up to 28%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have worked on validating and comparing losses from Hazus to real events (Kircher et al, 2006; National Institute of Building Sciences (NIBS), 2001; Remo and Pinter, 2012; Wald et al, 2020). The NIBS (2001) study examined only earthquakes in California and found that using site-specific soil types and actual building inventories could improve loss estimates by 10%–30% and up to 28%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that utilizing site-specific soil data resulted in a reduction of 8%–41% in estimated losses. Most recently, Wald et al (2020) compared Hazus and PAGER losses to each other for scenario events and to actual losses for real events. They compared 14 actual events and 10 scenario events, and of those 5 of each were located in the CEUS and concluded that Hazus estimates are consistently larger than reported economic losses (with loss ratios ranging from 1.3 to 16), especially for lower-magnitude events ( M < 6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations